Penegakan Hukum dalam Kasus Perlindungan Satwa Liar: Kajian Sosiologi Hukum tentang Keadilan dan Ketimpangan Sosial - Pramana, Mario Adiluz; Rato, Dominikus; Ohoiwutun, Y.A Triana (IAI Nasional Laa Roiba Bogor, 2025)
Law enforcement in wildlife protection is a crucial issue involving environmental, legal and social justice aspects. This article examines the dynamics of law enforcement in wildlife protection cases through a legal sociology approach, with a focus on issues of justice and social inequality. Although various regulations have been implemented to protect endangered wildlife, the effectiveness of law enforcement remains weak and often uneven. Factors such as social inequality, corruption, and economic power exacerbate wildlife law violations. Émile Durkheim's sociological theory can be connected to the case of wildlife protection through the social concepts he developed, such as social solidarity, collective morality, and the function of law in society. Local communities, especially those who live around conservation areas, are often the ones most affected by conservation policies, while violations by economically powerful groups are not always subject to appropriate sanctions. This analysis shows that unfair law enforcement and inequality in access to justice affect the success of wildlife conservation efforts. Therefore, a more inclusive and fair approach is needed in the application of the law, which not only protects wildlife but also ensures justice for the communities involved. This article concludes that increasing the effectiveness of law enforcement, strengthening regulations, and empowering local communities are important steps to overcome social inequality in the case of wildlife protection, so as to create a balance between environmental conservation and social justice.